To the issue of determining evaluative and aesthetic estimate of future primary school teachers (Pedagogy of Higher and Secondary Education, 2014)
Gorshchenko Y. А. To the issue of determining evaluative and aesthetic estimate of future primary school teachers.The article deals with the issue of developing evaluative and aesthetic estimate of future primary school teachers using different kinds of art. The author gives an analysis of scholarly literature and characterizes such concepts as “aesthetic estimate”, “evaluative estimate”, “evaluative and aesthetic estimate”.
Keywords: evaluative and aesthetic estimate; aesthetic estimate; evaluative estimate; future primary school teachers